Rumination in Everyday Life: The Influence of Distancing, Immersion, and Distraction. Issue 2 (May 2016) - Yasinski, Carly; Hayes, Adele M.; Laurenceau, Jean-Philippe
Rumination has been consistently associated with the development and maintenance of a variety of psychological disorders. While recent research has investigated a number of strategies to counter rumination and its negative effects, few have investigated their efficacy outside of a clinical or laboratory context. The current study used a daily diary methodology to compare the efficacy of three such strategies in the everyday lives of a highly ruminative sample. Over the course of 10 days, participants (N = 154) were asked to apply one of three perspectives (distanced, immersed, or distraction) to their thoughts and emotions about the most stressful event of the day and then to write a short narrative about the event. Over the 10-day period, immersion was associated with an average increase in negative emotion from before to after the narrative, whereas distancing was associated with little reactivity, and distraction was associated with a decrease in negative emotion. Participants in the distanced condition showed less ruminative, unproductive processing and used fewer negative emotion words in the narratives than those in the immersed condition. These differences were maintained over the 10-day study period. In targeted analyses of the days with the highest level of ruminative processing and/or event-related stress for each individual, the distanced and immersed groups reported similar levels of negative emotion reactivity and word use, but the distanced group showed less ruminative processing in the narratives. An interaction emerged suggesting that ruminative processing was only associated with an increase in negative emotion in the immersed group and not in the distanced group. The findings are discussed in the context of decreasing risk for depression and related disorders by targeting emotion regulation strategies on a daily level.